Predictors of pulmonary embolism in chronic obstructive pulmonary diseases patients admitted for worsening respiratory symptoms: An individual participant data meta-analyses - Mismetti, Valentine; Couturaud, Francis; Sanchez, Olivier; Morillo, Raquel; Ollier, Edouard; Rodriguez, Carmen; Roy, Pierre-Marie; Ruiz-Artacho, Pedro; Gagnadoux, Frédéric; Le-Mao, Raphael; Tabernero, Eva; Nonent, Michel; et al. (European journal of internal medicine, 2025)
•In COPD patients admitted for worsening respiratory symptoms, Pulmonary Embolism is not rare, but systematic screening does not improve patient's prognosis•We analyzed individual data of COPD patients admitted in two prospective trials of PE screening, to assess for potential predictors•an increase in BNP levels and respiratory rate ≥ 30 min were associated with an increased risk of Pulmonary Embolism, but with a low discriminant power. Pulmonary embolism (PE) and acute exacerbation of chronic obstructive pulmonary disease (COPD) have similar clinical symptoms, making PE diagnosis challenging. Previous studies have shown that the prevalence of PE among COPD patients admitted with worsening respiratory symptoms was not negligible, but that systematic search for PE did not provide a clinical benefit. Predictive factors for PE remain unknown. to identify predictive factors for PE among COPD patients with worsening respiratory symptoms. We conducted an individual participant data meta-analysis which included the patients from the prospective PEP cohort and those randomized to the intervention arm in the SLICE trial which included a systematic search for PE in COPD patients admitted for worsening respiratory symptoms. Univariable and multivariable analysis were used to assess factors associated with the diagnosis of PE during the initial management. Among 1110 COPD patients, PE was diagnosed in 61 (5.49 %; 95 %CI 4.15 %-6.84 %). In univariable analysis, BNP (Brain natriuretic peptide) (odds ratio [OR] 1.02 per 100 ng/L increase, 95 %CI 1.01–1.04), prothrombin time (OR 0.78, 95 %CI 0.65–0.94), fibrinogen (OR 0.80, 95 %CI 0.64–0.98), atrial fibrillation (OR 4.74, 95 %CI 1.84–10.80), respiratory rate ≥30 min (OR 2.34, 95 %CI 1.13–4.6) and recent medical immobilization (OR 1.79, 95 %CI 0.99–3.13]) were associated with the risk of PE diagnosed during the initial management. In multivariable analysis, respiratory rate ≥30 (OR 2.77, 95 %CI 1.08–6.71) was a predictive factor for PE, as well as BNP (OR 1.02, 95 %CI 1.00–1.05) with an area under the curve =0.64, negative predictive value =0.15 (95 %CI 0.09–0.23), sensitivity =0.78 (95 %CI 0.74–0.82) and specificity =0.46 (95 %CI 0.29–0.63). Among patients with COPD admitted for worsening respiratory symptoms, respiratory rate and BNP levels are predictor of PE, but with limited discriminatory power.